A banánhéj. Beszélgetés az Angelica kávéházban
critic Péter Molnár Gál, actor Dénes Újlaky, politician Imre Pozsgay, politician and lawyer Dr. Balázs Horváth, program host Péter Rózsa, small mistakes and lapses that may cause tragedy, Péter Gárdos